KONTEKSTTE ATLÍQ SÓZLERDIŃ KÓP MÁNILILIGINIŃ SÁWLELENIW ÓZGEShELIKLERI (T.JUMAMURATOV ShÍǴARMALARÍ TIYKARÍNDA) - Uzaqbaeva, Salima Muratbaevna (SCIENCE and SOCIETY, 2026)
The article analyzes the nature of polysemous words and homonyms in the Karakalpak language, their differences, and semantic features from a scientific perspective. Based on the theoretical views of scholar A. Musabayev, the degree of semantic divergence of words with the same form has been analyzed. Literary examples from the works demonstrate the contextual meanings of polysemous words derived from nouns like head, height, face, mouth, and face as well as the development of their usage in language.